Ultrathin rigid phenolic aerogel heat insulation sheet and preparation method thereof

By introducing sodium silicate solution into the fiber felt to enhance rigidity, and combining it with phenolic aerogel precursor solution filling and hot melt adhesive film composite, the problems of fragility and insufficient rigidity of existing aerogel insulation materials at high temperatures are solved, achieving comprehensive performance of ultra-thin, high rigidity and excellent thermal insulation.

CN121375170APending Publication Date: 2026-01-23SUZHOU HANGYU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511480531.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing aerogel insulation materials are easily broken under high-temperature flame impact, lack rigidity, and have poor ablation resistance, making it difficult to prepare them into ultra-thin and highly rigid forms, thus failing to meet the requirements for high-performance insulation.

Method used

By preparing a fiber felt rigidification solution, using inorganic solutions such as sodium silicate to enhance the rigidity of the fiber felt, and combining it with a phenolic aerogel precursor solution for filling and curing, a rigid phenolic aerogel composite material is formed. A hot melt adhesive film is then laid on the surface, and a gradient heating and hot pressing composite process is adopted to ensure the rigidity and high temperature resistance of the material.

Benefits of technology

It achieves ultra-thin heat insulation sheets that are not burned through under high-temperature flames, possessing high compressive strength and excellent heat insulation performance, as well as high rigidity and excellent ablation resistance, making it suitable for safe evacuation and emergency response in high-temperature environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an ultrathin rigid phenolic aerogel heat insulation sheet and a preparation method thereof, and belongs to the field of heat insulation materials. The preparation method comprises the following steps: firstly, impregnating a fibrofelt in a sodium silicate-based rigidifying solution, and carrying out mould pressing and drying to form a self-supporting rigid framework; then, the framework is soaked in a phenolic aerogel precursor solution, curing, washing and drying are carried out, and framework pores are filled with phenolic aerogel; and finally compounding the hot melt adhesive film. According to the preparation method, through the specific process sequence of first rigidifying and then compounding, the problems that a traditional aerogel material is poor in rigidity and prone to pulverization, and a silicon dioxide-based material is insufficient in ultra-high-temperature ablation resistance are successfully solved, and the thickness of the obtained heat resisting sheet is 0.1-5 mm; the composite material has excellent rigidity (the compression strength is greater than 2MPa when the deformation quantity is 5%), low heat conductivity coefficient (0.02-0.045 W / (m.K)) and excellent 1200 DEG C high-temperature flame ablation resistance, and is especially suitable for thermal protection in limited spaces such as new energy batteries and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermal insulation materials, specifically, it relates to an ultrathin rigid phenolic aerogel thermal insulation sheet and its preparation method. Background Technology

[0002] In recent years, the rapid development of new energy power batteries and energy storage has created an urgent demand for high-performance thermal insulation materials. These materials not only need to possess excellent thermal insulation performance, but also need to provide long-term thermal protection within limited installation space (such as between battery cells). Especially in extreme situations such as battery thermal runaway, thermal insulation materials must be able to withstand instantaneous high-temperature flame impact and prolonged ablation, buying valuable time for safe evacuation and emergency response.

[0003] Aerogel materials, due to their unique nanoporous structure, have extremely low thermal conductivity, making them ideal candidates for high-efficiency thermal insulation. Currently, the mainstream products on the market are thermal insulation sheets or felts based on silica aerogel. However, these materials have obvious limitations: (1) Poor mechanical properties: Silica aerogel is inherently brittle, and its composite materials are prone to pulverization and breakage under pressure, making it difficult to ensure structural integrity under long-term vibration or compression environments; (2) Insufficient resistance to ultra-high temperature flame ablation: Under the impact of high-temperature flames (such as above 1200℃) generated by cell deflagration or explosion, the silica skeleton will undergo sintering shrinkage and structural collapse, leading to rapid failure of the thermal insulation function; (3) Limitations in shape and rigidity: It is difficult to prepare a shape that combines ultra-thinness (such as <5mm) and high rigidity. Existing products are mostly soft blanket-like or thick plate-like, which cannot meet the requirements of precision assembly scenarios with strict requirements for deformation, that is, maintaining structural stability and providing sufficient support strength under low deformation.

[0004] To address this, the industry has explored composite solutions incorporating phenolic resin and silica aerogel into fiber felts in hopes of improving performance. However, these solutions have not fundamentally solved the problem: First, the lack of rigidity remains unresolved. In these solutions, phenolic resin is typically used only as a surface or interlayer binder for the fibers, and its quantity and function are insufficient to transform the loose fiber felt into a self-supporting rigid skeleton. Therefore, the final product still lacks sufficient compressive strength and resistance to deformation on a macroscopic scale. Second, the bottleneck of resistance to ultra-high temperature ablation persists. The primary insulation component in these solutions remains silica. As mentioned earlier, silica sintersulates and densifies at temperatures exceeding 1000°C, leading to insulation failure. Meanwhile, the phenolic resin used as a binder may pyrolyze at high temperatures, which may damage the interlayer bonding and accelerate the structural damage of the material. Finally, there is a contradiction between the component function and the structural design. Existing technologies have failed to solve the contradiction between rigidity and high-temperature insulation through innovation in material design and process sequence. Simple physical blending or simple sequential compounding often results in materials that are either too flexible but not rigid enough, or sacrifice long-term thermal stability by introducing a binder phase that is not resistant to high temperatures.

[0005] Therefore, there is an urgent need in this field for an innovative material system and preparation method that can break through existing technical thinking and produce an integrated composite material that combines high rigidity, excellent thermal insulation and outstanding ablation resistance at an ultra-thin scale. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide an ultrathin rigid phenolic aerogel thermal insulation sheet and its preparation method, the details of which are as follows: A method for producing an ultrathin rigid phenolic aerogel insulation sheet includes the following steps: (1) Preparation of fiber felt rigidification solution: Sodium silicate, silane coupling agent and solvent are mixed evenly at a mass ratio of 1:(0.5~2):(4~9) to obtain a solution for enhancing the rigidity of fiber felt; the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, methacryloyloxyfunctional silane, methyltrimethoxysilane and dimethyldimethoxysilane; the solvent is at least one of deionized water and ethanol; (2) Preparation of rigid fiber felt: The fiber felt with a thickness of 0.1~5 mm is immersed in the fiber felt rigidification solution obtained in step (1) to allow the solution to fully penetrate the fiber skeleton. Then, it is molded and dried to solidify and shape the fiber felt into a rigid structure to obtain rigid fiber felt; the fiber felt is glass fiber needle-punched felt, quartz fiber needle-punched felt, alumina fiber needle-punched felt, alumina fiber needle-punched felt or pre-oxidized fiber needle-punched felt; (3) Preparation of phenolic aerogel precursor solution: Phenolic resin, modifier, curing agent and solvent are mixed evenly in a mass ratio of 1:(0.05~0.2):(0.01~0.3):(1~9) to obtain phenolic aerogel precursor solution; the modifier is at least one of boric acid, tetraethyl orthosilicate, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, aluminum isopropoxide and zirconium propoxide; the curing agent is at least one of hexamethylenetetramine, p-toluenesulfonic acid, aniline, sodium hydroxide, sodium bicarbonate and ammonia water; the solvent is at least one of methanol, ethanol, ethylene glycol, acetone and deionized water; (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is impregnated in the phenolic aerogel precursor solution obtained in step (3), and then cured, washed and dried in sequence to obtain rigid phenolic aerogel composite material. (5) Composite hot melt adhesive film: hot melt adhesive film is laid on the upper and lower surfaces of the rigid phenolic aerogel composite material obtained in step (4), and then hot-pressed composite is performed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet; the hot melt adhesive film is at least one of polyester hot melt adhesive film, polyimide hot melt adhesive film, and polyethylene terephthalate hot melt adhesive film, with a thickness of 0.02~0.5mm.

[0007] Further, in step (2), the molding process is to press the impregnated fiber felt in a mold of a defined thickness to control the final thickness and density of the rigid fiber felt.

[0008] Furthermore, the molding process specifically involves placing the impregnated fiber felt within a metal frame with a thickness of 0.1–5 mm, covering the upper and lower surfaces of the metal frame with metal plates, and then applying pressure to lock it in place. Through this molding process, particularly by applying pressure within a mold or metal frame of a defined thickness, the final thickness and density of the rigid fiber felt can be precisely controlled. This not only ensures the preparation of ultra-thin final products with extremely small thickness tolerances but also guarantees the uniformity and density of the fiber skeleton, laying a solid foundation for the subsequent composite of a uniform aerogel matrix, thereby improving the consistency of product performance.

[0009] Furthermore, in steps (2) and (4), the drying temperature is 60~110℃. Controlling the drying temperature at 60~110℃ can efficiently remove solvents and moisture while avoiding damage to the rigid layer of the fiber felt or the phenolic aerogel network structure due to excessively high temperatures, and also avoids insufficient drying due to excessively low temperatures, effectively ensuring production efficiency and the structural integrity of the product.

[0010] Further, in step (4), the curing process includes: first, maintaining the temperature at 60~110℃ for 3~12 hours, and then maintaining the temperature at 150~200℃ for 12~24 hours. This two-stage gradient heating process facilitates the gradual and thorough cross-linking and curing of the phenolic resin, avoiding internal stress and cracks caused by excessively rapid or intense reactions, thereby obtaining a phenolic aerogel with a more complete three-dimensional network structure and superior mechanical properties.

[0011] Furthermore, in step (4), the washing process involves rinsing with circulating water at 80°C for 12-24 hours. Rinsing with circulating water at 80°C for 12-24 hours can efficiently and thoroughly remove small molecule byproducts such as salts and residual solvents generated during the curing process of the composite material, significantly improving the chemical purity of the product. This avoids performance degradation caused by the volatilization or decomposition of impurities at high temperatures, and also improves the thermal stability and service life of the material under long-term high-temperature use.

[0012] Furthermore, in step (5), the conditions for hot-pressing composite are: pressure 3~5 MPa, temperature 40~150℃, and time 0.5~2 min. Controlling the hot-pressing composite conditions within this range ensures that the hot melt adhesive film fully melts and forms a strong bonding interface with the composite matrix, while effectively avoiding excessive pressure or temperature from causing compression collapse or thermal degradation of the fragile porous aerogel structure inside. This achieves a stable interface bond and perfect protection of the internal nano-insulation structure.

[0013] The present invention also provides an ultrathin rigid phenolic aerogel insulation sheet, comprising: A rigid phenolic aerogel composite matrix, wherein the matrix is ​​composed of a rigid fiber felt as a skeleton, and its pores are filled with phenolic aerogel prepared by a sol-gel process. Hot melt adhesive film layer covering the upper and lower surfaces of the composite matrix.

[0014] Furthermore, the rigid fiber felt is formed by impregnation with sodium silicate solution followed by molding and drying. The fact that the rigid fiber felt is formed by impregnation with sodium silicate solution followed by molding and drying ensures that the fiber skeleton has sufficient rigidity and strength, which is a fundamental prerequisite for the final insulation sheet to achieve high compressive strength (greater than 2 MPa with 5% deformation) and structural stability under low deformation.

[0015] Furthermore, the thermal insulation sheet has a room temperature thermal conductivity of 0.02~0.045 W / (m·K), a thickness of 0.1~5 mm, and a compressive strength greater than 2 MPa at 5% deformation. These quantitative indicators collectively demonstrate that the product of this invention successfully achieves a balance between ultra-thinness, high-efficiency thermal insulation, and high mechanical strength, with overall performance indicators superior to existing similar materials.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: Unlike existing technologies that use silica as the primary insulating phase, this invention creatively selects phenolic aerogel, formed from phenolic resin through a sol-gel process, as the core insulating matrix. When exposed to high-temperature flames, this matrix does not passively withstand the heat but actively undergoes pyrolysis. This generates non-flammable gases, forming a gaseous barrier (thermal blocking effect), and simultaneously creates a stable carbon layer to block radiative heat transfer. Crucially, the pre-constructed inorganic rigid framework of this invention provides stable physical support for the pyrolysis and carbonization process of the phenolic aerogel at high temperatures, preventing shrinkage, pulverization, or structural collapse of pure aerogels or disordered composite materials at high temperatures, ensuring the formation of a dense and complete carbon protective layer. This synergy between the rigid framework and the intelligent matrix allows the material to withstand prolonged exposure to flames at 1200°C without being burned through. In contrast, existing technologies rely on silica insulating matrices that sinter and shrink at temperatures exceeding 1000°C, leading to the collapse of the nanoporous structure and rapid failure of the insulating function. Furthermore, the phenolic resin used as an interlayer binder in existing technologies delaminates after high-temperature pyrolysis, further accelerating the degradation.

[0017] II. The core of this invention lies in the step of "pre-rigidifying the fiber felt with an inorganic solution such as sodium silicate," which constructs a robust microstructure. This is fundamentally different from existing technologies that only use low-content phenolic resin for fiber surface bonding (aimed at improving felting properties and abrasion resistance) and use phenolic resin as a slurry binder (aimed at bonding silica powder and lamination). The process sequence of this invention ensures that the fiber felt itself first transforms into a self-supporting rigid body, and then the phenolic aerogel precursor fills its pores and solidifies. This specific sequence and structure enable the composite material to achieve a fundamental rigid transformation, obtaining extremely high compressive strength (greater than 2 MPa with a deformation of 5%, and generally higher than 3.5 MPa in the examples) and excellent dimensional stability. If this rigidification step is omitted, the compressive strength of the resulting composite material (0.5 MPa) will drop sharply by about 85-90%, failing to meet the high rigidity requirements of this invention, highlighting the indispensability of this step in achieving a fundamental rigid transformation of the material. Detailed Implementation

[0018] To enable those skilled in the art to understand the features and effects of this application, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art in this application, and in case of conflict, the definitions in this specification shall prevail.

[0019] The present application will be described below with reference to specific embodiments and examples. It should be understood that these specific embodiments and examples are merely illustrative and are not intended to limit the scope or use of the present application.

[0020] Unless otherwise stated, the methods, reagents, and conditions used in the preparation examples, comparative examples, and embodiments described below are conventional methods, reagents, and conditions in the art.

[0021] Unless otherwise specified, in this application, parts by weight represent the relative number of mass parts in the composition, which can be any mass unit, such as, but not limited to, kilograms, grams, etc.

[0022] The specific embodiments are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0023] Example 1 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 1.2 kg of γ-aminopropyltriethoxysilane and 6.0 kg of deionized water, put them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0024] (2) Preparation of rigid fiber felt: Take a piece of quartz fiber needle-punched felt with a thickness of 1 mm and completely immerse it in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 1 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 80°C to cure the sodium silicate and obtain the shaped rigid fiber felt.

[0025] (3) Preparation of phenolic aerogel precursor solution: Weigh 5.0 kg of phenolic resin, 0.5 kg of boric acid, 0.5 kg of hexamethylenetetramine and 25.0 kg of ethanol, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0026] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, placed in an oven at 80°C for 6 hours, and then transferred to an oven at 180°C for 18 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 18 hours to thoroughly remove residual salts and solvents. Finally, it is dried in an oven at 80°C to obtain the rigid phenolic aerogel composite material.

[0027] (5) Composite hot melt adhesive film: A layer of polyimide hot melt adhesive film with a thickness of 0.05 mm is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 1 minute at a pressure of 4 MPa and a temperature of 120°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0028] Example 2 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 0.5 kg of methyltrimethoxysilane and 9.0 kg of ethanol, put them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0029] (2) Preparation of rigid fiber felt: Take a piece of glass fiber needle-punched felt with a thickness of 0.1 mm and immerse it completely in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 0.1 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 80°C to cure the sodium silicate and obtain the shaped rigid fiber felt.

[0030] (3) Preparation of phenolic aerogel precursor solution: Weigh 2.0 kg of phenolic resin, 0.1 kg of tetraethyl orthosilicate, 0.04 kg of p-toluenesulfonic acid and 18.0 kg of deionized water, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0031] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, placed in an oven at 60°C for 12 hours, and then transferred to an oven at 150°C for 24 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 24 hours to thoroughly remove residual salts and solvents. Finally, it is dried in a drying oven at 60°C to obtain the rigid phenolic aerogel composite material.

[0032] (5) Composite hot melt adhesive film: A layer of 0.02 mm thick polyester hot melt adhesive film is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 2 minutes at a pressure of 3 MPa and a temperature of 40 °C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0033] Example 3 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 2.0 kg of dimethyldimethoxysilane and 4.0 kg of deionized water, put them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0034] (2) Preparation of rigid fiber felt: Take a piece of aluminosilicate fiber needle-punched felt with a thickness of 5 mm, and completely immerse it in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 5 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 110°C to cure the sodium silicate and obtain a shaped rigid fiber felt.

[0035] (3) Preparation of phenolic aerogel precursor solution: Weigh 1.0 kg of phenolic resin, 0.2 kg of aluminum isopropoxide, 0.3 kg of ammonia (concentration 25%) and 1.0 kg of methanol, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0036] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, first placed in an oven at 110°C for 3 hours, and then transferred to an oven at 200°C for 12 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 12 hours to thoroughly remove residual salts and solvents. Finally, it is dried in a drying oven at 110°C to obtain the rigid phenolic aerogel composite material.

[0037] (5) Composite hot melt adhesive film: A layer of polyethylene terephthalate hot melt adhesive film with a thickness of 0.5 mm is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 0.5 minutes at a pressure of 5 MPa and a temperature of 150°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0038] Example 4 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 1.3 kg of γ-glycidyl etheroxypropyltrimethoxysilane and 7.0 kg of deionized water, put them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0039] (2) Preparation of rigid fiber felt: Take a piece of alumina fiber needle-punched felt with a thickness of 2 mm and immerse it completely in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 1 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 80°C to cure the sodium silicate and obtain the shaped rigid fiber felt.

[0040] (3) Preparation of phenolic aerogel precursor solution: Weigh 4.0 kg of phenolic resin, 0.2 kg of γ-aminopropyltriethoxysilane, 0.3 kg of aniline and 20.0 kg of ethylene glycol, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0041] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, first placed in an oven at 90°C for 8 hours, and then transferred to an oven at 170°C for 20 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 15 hours to thoroughly remove residual salts and solvents. Finally, it is dried in an oven at 80°C to obtain the rigid phenolic aerogel composite material.

[0042] (5) Composite hot melt adhesive film: A layer of polyimide hot melt adhesive film with a thickness of 0.05 mm is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 1 minute at a pressure of 4 MPa and a temperature of 120°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0043] Example 5 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 1.6 kg of methacryloyloxypropyltrimethoxysilane, and 5.0 kg of a mixed solvent of ethanol and deionized water (mass ratio 1:1), place them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0044] (2) Preparation of rigid fiber felt: Take a piece of pre-oxidized fiber needle-punched felt with a thickness of 3 mm, and completely immerse it in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 3 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 80°C to cure the sodium silicate and obtain the shaped rigid fiber felt.

[0045] (3) Preparation of phenolic aerogel precursor solution: Weigh 3.0 kg of phenolic resin, 0.24 kg of zirconium n-propoxide, 0.03 kg of sodium hydroxide and 12.0 kg of acetone, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0046] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, first placed in an oven at 70°C for 10 hours, and then transferred to an oven at 160°C for 22 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 20 hours to thoroughly remove residual salts and solvents. Finally, it is dried in an oven at 80°C to obtain the rigid phenolic aerogel composite material.

[0047] (5) Composite hot melt adhesive film: A layer of polyimide hot melt adhesive film with a thickness of 0.05 mm is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 1 minute at a pressure of 4 MPa and a temperature of 120°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0048] Example 6 (1) Preparation of fiber felt rigidification solution: Weigh 1.0 kg of sodium silicate, 1.5 kg of γ-aminopropyltriethoxysilane and 6.0 kg of deionized water, put them in a container and stir until they are mixed evenly to obtain a clear fiber felt rigidification solution.

[0049] (2) Preparation of rigid fiber felt: Take a piece of quartz fiber needle-punched felt with a thickness of 1 mm and completely immerse it in the solution obtained in step (1) to ensure that the solution fully penetrates the fiber skeleton. After taking it out, place it in a metal frame with an inner cavity thickness of 1 mm, cover the upper and lower surfaces of the metal frame with flat metal plates, and tighten them with bolts. Then put the entire mold into a drying oven and dry it at 80°C to cure the sodium silicate and obtain the shaped rigid fiber felt.

[0050] (3) Preparation of phenolic aerogel precursor solution: Weigh 5.0 kg of phenolic resin, 0.75 kg of boric acid, 1.5 kg of sodium bicarbonate, and 15.0 kg of methanol and deionized water mixed solvent (mass ratio 1:1). Mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0051] (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is completely impregnated in the precursor solution obtained in step (3). After removal, it is sealed in a mold, first placed in an oven at 100°C for 5 hours, and then transferred to an oven at 190°C for 15 hours to complete curing. The cured composite material is removed from the mold and washed in a circulating water bath at 80°C for 20 hours to thoroughly remove residual salts and solvents. Finally, it is dried in an oven at 80°C to obtain the rigid phenolic aerogel composite material.

[0052] (5) Composite hot melt adhesive film: A layer of polyimide hot melt adhesive film with a thickness of 0.05 mm is laid on the upper and lower surfaces of the composite material obtained in step (4), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 1 minute at a pressure of 4 MPa and a temperature of 120°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0053] Comparative Example 1 This comparative example uses the sequence of "fiber mat → phenolic resin bonding → silica aerogel filling" to prepare the composite material: (1) Preparation of phenolic resin binder solution: Prepare a water-soluble phenolic resin solution with a mass fraction of 15% (molecular weight of about 2500).

[0054] (2) Preparation of bonded fiber felt: The glass fiber needle-punched felt with a thickness of 2 mm was impregnated with the above phenolic resin solution by spraying, and then cured at 210°C for 5 minutes to obtain the surface bonded glass fiber felt.

[0055] (3) Preparation of silica aerogel precursor solution: Tetraethyl orthosilicate, ethanol, deionized water and hydrochloric acid are mixed in a certain proportion and hydrolyzed to obtain silica sol.

[0056] (4) Preparation of composite material: The bonding fiber felt obtained in step 2 is placed in a mold, and the silica sol obtained in step 3 is injected. The mixture is allowed to stand and gel for 20 minutes at 40°C and 0.8 MPa. Then it is aged in ethanol at 50°C for 30 hours.

[0057] (5) Drying treatment: The aged sample was dried at 80°C and normal pressure for 48 hours to obtain the composite material.

[0058] Comparative Example 2 This comparative example uses the sequence of "fiber felt → (phenolic resin + silica powder) slurry blending and impregnation" to prepare composite materials: (1) Preparation of blended slurry: Phenolic resin, silica aerogel powder, hexamethylenetetramine (curing agent) and deionized water are mixed in a mass ratio of 60:70:0.5:20 and stirred evenly to obtain aerogel slurry.

[0059] (2) Preparation of composite material preform: Impregnate a glass fiber needle-punched felt with a thickness of 2 mm in the above slurry to ensure full penetration.

[0060] (3) Stacking and curing: Take out a piece of impregnated fiber felt, place it in a mold, and cure it under a stepped heating process of 90℃ for 2 hours, 110℃ for 2 hours, and 150℃ for 2 hours to obtain the composite material of Comparative Example 2.

[0061] Comparative Example 3 (Variation of this application without rigidification steps) This comparative example is used to illustrate the impact of omitting the key "fiber felt rigidification" step of this invention: (1) Preparation of phenolic aerogel precursor solution: Weigh 5.0 kg of phenolic resin, 0.5 kg of boric acid, 0.5 kg of hexamethylenetetramine and 25.0 kg of ethanol, mix and stir until completely dissolved to obtain a uniform phenolic aerogel precursor solution.

[0062] (2) Preparation of rigid phenolic aerogel composite material: A 2 mm thick glass fiber needle-punched felt was completely impregnated in the precursor solution obtained in step (1). After removal, it was sealed in a mold, placed in an oven at 80°C for 6 hours, and then transferred to an oven at 180°C for 18 hours to complete curing. The cured composite material was removed from the mold and washed in an 80°C circulating water bath for 18 hours to thoroughly remove residual salts and solvents. Finally, it was dried in an 80°C drying oven to obtain the rigid phenolic aerogel composite material.

[0063] (3) Composite hot melt adhesive film: A layer of polyimide hot melt adhesive film with a thickness of 0.05 mm is laid on the upper and lower surfaces of the composite material obtained in step (2), and then a layer of release paper is placed on the upper and lower surfaces. It is placed in a hot press and hot-pressed for 1 minute at a pressure of 4 MPa and a temperature of 120°C. The release paper is then removed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet.

[0064] The materials obtained in Examples 1-6 and Comparative Examples 1-3 of the present invention were subjected to performance tests, and the test items are as follows: 1. Thermal conductivity: According to GB / T 10295-2008 (heat flow meter method), the thermal conductivity of the sample at 25℃ is measured using a thermal conductivity meter.

[0065] 2. Compression performance: The compressive strength of the sample at 5% deformation was determined according to GB / T 13480-2014.

[0066] 3. Ablation resistance: Custom test. Use a butane torch (flame center temperature 1200±50℃) to vertically align with the sample surface (1mm thick sample), with the flame center 10mm away from the sample surface. Record the temperature on the back of the sample after 30 minutes, as well as whether it is burned through and the time it takes to burn through.

[0067] The test results are shown in the table below: Test Project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Thickness (mm) 2.0 1.0 2.1 1.8 1.6 2.2 2.1 2.3 2.1 Thermal conductivity at room temperature (W / (m·K)) 0.028 0.032 0.030 0.029 0.031 0.028 0.026 0.035 0.029 Compressive strength (MPa) at 5% deformation 3.5 4.2 3.6 3.8 4.0 4.1 0.8 1.2 0.5 High-temperature flame test (1200℃, 30min) Not burned through, structurally intact Not burned through, structurally intact Not burned through, structurally intact Not burned through, structurally intact Not burned through, structurally intact Not burned through, structurally intact Burn-through, structural collapse Layering, severe powdering It wasn't burned through, but it was severely deformed. Macro-structural characteristics Overall rigidity, dimensional stability Overall rigidity, dimensional stability Overall rigidity, dimensional stability Overall rigidity, dimensional stability Overall rigidity, dimensional stability Overall rigidity, dimensional stability It is soft overall and easily deformed. The interlayer bonding is weak, and it is prone to delamination. Overall soft and lacking support Analyze the tabular data 1. Regarding rigid structures (compared with Comparative Examples 1, 2, and 3): Examples 1-6 of this invention demonstrate extremely high compressive strength (>3.5 MPa), which is attributed to a "pre-rigidification" step. This step transforms loose fiber mat into a self-supporting rigid body by forming a strong inorganic bond between the fiber skeleton using a sodium silicate solution.

[0068] In Comparative Example 1, the phenolic resin was only used for surface bonding during fiber felting and did not form a rigid skeleton that ran through the entire structure, resulting in extremely low compressive strength. In Comparative Example 2, the phenolic resin, as a slurry binder, mainly served to bond silica powder to the fibers and between layers, but it did not make the fiber felt itself rigid, and the resin decomposition at high temperatures easily led to delamination.

[0069] Comparative Example 3 directly demonstrates that without a rigidification step, even with phenolic aerogel filling, the composite material suffers from low strength due to the lack of a rigid framework. This highlights the critical importance of the "sequence": a rigid framework must be constructed first, followed by the filling of the insulating matrix.

[0070] 2. Regarding high-temperature ablation resistance (compared with Comparative Examples 1 and 2): This invention uses phenolic aerogel as the thermal insulation matrix. It undergoes intelligent pyrolysis at high temperatures, generating an inert gas and a stable carbon protective layer, achieving a gas-solid synergistic active thermal insulation mechanism. Therefore, it does not burn through for extended periods under a 1200°C flame. Comparative Examples 1 and 2 both use silica as the main thermal insulation phase. Silica undergoes sintering shrinkage at temperatures exceeding 1000°C, leading to the collapse of its nanoporous structure and rapid failure of its thermal insulation function; therefore, both were burned through or severely damaged during testing.

[0071] This invention successfully integrates high rigidity, ultra-thinness, excellent thermal insulation, and superior ablation resistance—properties that are difficult to achieve simultaneously in existing technologies—through a specific, non-obvious process sequence of "first constructing an inorganic rigid framework, then filling it with ablation-resistant phenolic aerogel." Comparative Examples 1 and 2 fully demonstrate that other process sequences cannot achieve the technical effects of this invention. Therefore, the technical solution described in this invention is not a simple superposition or conventional optimization of existing technologies, but rather possesses outstanding substantive features and significant progress.

[0072] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing an ultrathin rigid phenolic aerogel insulation sheet, characterized in that, Includes the following steps: (1) Preparation of fiber felt rigidification solution: Sodium silicate, silane coupling agent and solvent are mixed evenly at a mass ratio of 1:(0.5~2):(4~9) to obtain a solution for enhancing the rigidity of fiber felt; The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, methacryloyloxysilane, methyltrimethoxysilane, and dimethyldimethoxysilane. The solvent is at least one of deionized water and ethanol; (2) Preparation of rigid fiber felt: Fiber felt with a thickness of 0.1~5 mm is immersed in the fiber felt rigidification solution obtained in step (1) so that the solution fully penetrates the fiber skeleton, and then molding and drying are performed so that the fiber felt is solidified and shaped into a rigid structure to obtain rigid fiber felt; The fiber mat is glass fiber needle-punched mat, quartz fiber needle-punched mat, aluminum silicate fiber needle-punched mat, alumina fiber needle-punched mat or pre-oxidized fiber needle-punched mat. (3) Preparation of phenolic aerogel precursor solution: Phenolic resin, modifier, curing agent and solvent are mixed evenly in a mass ratio of 1: (0.05~0.2): (0.01~0.3): (1~9) to obtain phenolic aerogel precursor solution; The modifier is at least one of boric acid, tetraethyl orthosilicate, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, aluminum isopropoxide, and zirconium propoxide. The curing agent is at least one of hexamethylenetetramine, p-toluenesulfonic acid, aniline, sodium hydroxide, sodium bicarbonate, and ammonia water; The solvent is at least one of methanol, ethanol, ethylene glycol, acetone, and deionized water; (4) Preparation of rigid phenolic aerogel composite material: The rigid fiber felt obtained in step (2) is impregnated in the phenolic aerogel precursor solution obtained in step (3), and then cured, washed and dried in sequence to obtain rigid phenolic aerogel composite material. (5) Composite hot melt adhesive film: hot melt adhesive film is laid on the upper and lower surfaces of the rigid phenolic aerogel composite material obtained in step (4), and then hot-pressed composite is performed to obtain the ultra-thin rigid phenolic aerogel heat insulation sheet. The hot melt adhesive film is at least one of polyester hot melt adhesive film, polyimide hot melt adhesive film, and polyethylene terephthalate hot melt adhesive film, and has a thickness of 0.02~0.5mm.

2. The preparation method according to claim 1, characterized in that, In step (2), the molding process is to press the impregnated fiber felt in a mold with a defined thickness to control the final thickness and density of the rigid fiber felt.

3. The preparation method according to claim 2, characterized in that, The molding process specifically involves placing the impregnated fiber felt inside a metal frame with a thickness of 0.1 to 5 mm, covering the upper and lower surfaces of the metal frame with metal plates, and then applying pressure to lock it in place.

4. The preparation method according to claim 1, characterized in that, In steps (2) and (4), the drying temperature is 60~110℃.

5. The preparation method according to claim 1, characterized in that, In step (4), the curing process includes: first keeping the temperature at 60~110℃ for 3~12 hours, and then keeping the temperature at 150~200℃ for 12~24 hours.

6. The preparation method according to claim 1, characterized in that, In step (4), the washing process involves rinsing with circulating water at 80°C for 12 to 24 hours.

7. The preparation method according to claim 1, characterized in that, In step (5), the conditions for hot-pressing composite are: pressure 3~5 MPa, temperature 40~150℃, and time 0.5~2 min.

8. An ultrathin rigid phenolic aerogel insulation sheet, characterized in that, include: A rigid phenolic aerogel composite matrix, wherein the matrix is ​​composed of a rigid fiber felt as a skeleton, and its pores are filled with phenolic aerogel prepared by a sol-gel process. Hot melt adhesive film layer covering the upper and lower surfaces of the composite matrix.

9. The ultrathin rigid phenolic aerogel insulation sheet according to claim 8, characterized in that: The rigid fiber felt is formed by impregnation with sodium silicate solution and then molding and drying.

10. The ultrathin rigid phenolic aerogel insulation sheet according to any one of claims 8 or 9, characterized in that: The thermal insulation sheet has a room temperature thermal conductivity of 0.02~0.045 W / (m·K), a thickness of 0.1~5 mm, and a compressive strength greater than 2 MPa at a deformation of 5%.

Citation Information

Cited By

  • Anti-migration film hot melt adhesive and preparation method thereof

    CN122127920A